Identification of T cell target antigens in glioblastoma stem-like cells using an integrated proteomics-based approach in patient specimens - Rapp, Carmen; Warta, Rolf; Geisenberger, Christoph; Gál, Zoltán; Rösch, Saskia; Dettling, Steffen; Jungk, Christine; Dao Trong, Huy Philip; Ahmadi, Rezvan; Sahm, Felix; Reuss, David; Herpel, Esther; et al. (Acta neuropathologica, 2017)
Glioblastoma (GBM) is a highly aggressive brain tumor and still remains incurable. Among others, an immature subpopulation of self-renewing and therapy-resistant tumor cells—often referred to as glioblastoma stem-like cells (GSCs)—has been shown to contribute to disease recurrence. To target these cells personalized immunotherapy has gained a lot of interest, e.g. by reactivating pre-existing anti-tumor immune responses against GSC antigens. To identify T cell targets commonly presented by GSCs and their differentiated counterpart, we used a proteomics-based separation of GSC proteins in combination with a T cell activation assay. Altogether, 713 proteins were identified by LC-ESI-MS/MS mass spectrometry. After a thorough filtering process, 32 proteins were chosen for further analyses. Immunogenicity of corresponding peptides was tested ex vivo. A considerable number of these antigens induced T cell responses in GBM patients but not in healthy donors. Moreover, most of them were overexpressed in primary GBM and also highly expressed in recurrent GBM tissues. Interestingly, expression of the most frequent T cell target antigens could also be confirmed in quiescent, slow-cycling GSCs isolated in high purity by the DEPArray technology. Finally, for a subset of these T cell target antigens, an association between expression levels and higher T cell infiltration as well as an increased expression of positive immune modulators was observed. In summary, we identified novel immunogenic proteins, which frequently induce tumor-specific T cell responses in GBM patients and were also detected in vitro in therapy-resistant quiescent, slow-cycling GSCs. Stable expression of these T cell targets in primary and recurrent GBM support their suitability for future clinical use.
Gesehen am 27.11.2018